Efektivitas Media Interaktif Aplikasi Kahoot dalam Pembelajaran Matematika untuk Meningkatkan Hasil Belajar Siswa Kelas 5 - Nugroho, Donny Cahyo; Trimurtini, Trimurtini; Ratnaningrum, Ika (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the improvement of mathematics learning outcomes of grade V students of SDN Bangunharjo through the use of the Kahoot application which is integrated with the Problem Based Learning model and analyze the level of effectiveness of its application in learning. The method used was an experiment with the Nonequivalent Control Group Design design which involved two classes, namely the experimental class and the control class, each consisting of 27 students. Data collection is carried out through the provision of pretests and posttests. Data analysis includes normality tests, homogeneity tests, Independent Samples t-tests, and N-Gain tests to determine the difference and magnitude of improvement in learning outcomes. The results showed a significant improvement in learning outcomes in the experimental class, with an average N-Gain of 0.56 (medium category) which was higher than that of the control class of 0.51 (low category). In addition, the results of the t-test showed a significance value of 0.002 < 0.05 which indicates a significant difference between the two classes. Therefore, it can be concluded that the use of the Kahoot application integrated with the PBL model is effective in improving the mathematics learning outcomes of elementary school students. Keywords: Kahoot, Problem Based Learning, math learning outcomes, interactive media, elementary school